Phytochemical contents and biological evaluation of Ruta chalepennsis L. growing in Saudi Arabia - Shorok M. Alotaibi; Monerah S. Saleem; Jehan G. Al-humaidi (Elsevier, 2018)
Phytochemical screening of Ruta chalepensis L. exhibited the presence of different chemical groups. The dried aerial parts of the plant was total extracted by ethanol and successively using chloroform, ethyl acetate and Butanol, out of the successive extracts four compounds namely, scopletin, kaempferol, quercetin, quercetin 3-O-α-L-rhamno glucopyranosyl (Rutin) were isolated and biological evaluations. Total ethanol and successive extracts; chloroform, ethyl acetate and Butanol were produced excellent antimicrobial activities against gram negative bacteria, gram positive bacteria and fungi. Ethyl acetate extract was the best for inhibition of the microorganism's growth. All extracts (total ethanol, and successive extracts) showed DPPH radical scavenging activity in a concentration-dependent manner. The best antioxidant activity was obtained by ethyl acetate & n-butanol extract (94.28%, IC50 = 56.6 µg/ml). Also All extracts (total ethanol, and successive extracts) showed anticoagulant activity at higher concentration with prolonged clotting time 6:30 and 4:30 s at 10 mg/ml concentrations, respectively. Keywords: Phytochemical analysis, Medicinal plants, Ruta chalepensis, Antimicrobial, Antioxidant, Anticoagulant